RESEARCH RESULTS ON THE USE OF INTERNET AS COMMUNICATION TOOL ACROSS VARIOUS GENERATION COHORTS IN INDONESIA - Indrajit, Richardus Eko (Majalah Ilmiah Matematika Komputer, 2006)
One of the traditional functions of public relations is to influence perceptions of internal and externalpublics through communication. In order to accomplish this, appropriate use of communicationchannels is necessary to send accurate and timely information to the target audiences. Presently, moreand more target audiences are equipped with information and communication technology that makethem enable to access internet as the whole new arena where publics interact in a network of onlinecomputers. It means that whatever messages that are coming to their life would be checked across theironline communities. This research is conducted to study the communication behaviors of the old andnew generations of internet users in Indonesia who are fond of connecting themselves to the cyberworld. The main targets are to investigate and to identify the impacts of their behaviors that challengethe existing public relations practices. The results of the study shows that there are similarities anddifferences among the four generations of people - namely Traditionalists, Baby Boomers, Xers, andMillennials - in conducting their online communication. Some of them are considered to have directimpacts on how public relations should be conducted today towards these online communities to gainthe expected results.